Trichothiodystrophy causative TFIIEβ mutation affects transcription in highly differentiated tissue - Theil, Arjan F.; Moog, Ute; Kotzaeridou, Urania (Human molecular genetics, 2017)
The rare recessive developmental disorder Trichothiodystrophy (TTD) is characterized by brittle hair and nails. Patients also present a variable set of poorly explained additional clinical features, including ichthyosis, impaired intelligence, developmental delay and anemia. About half of TTD patients are photosensitive due to inherited defects in the DNA repair and transcription factor II H (TFIIH). The pathophysiological contributions of unrepaired DNA lesions and impaired transcription have not been dissected yet. Here, we functionally characterize the consequence of a homozygous missense mutation in the general transcription factor II E, subunit 2 (GTF2E2/TFIIEβ) of two unrelated non-photosensitive TTD (NPS-TTD) families. We demonstrate that mutant TFIIEβ strongly reduces the total amount of the entire TFIIE complex, with a remarkable temperature-sensitive transcription defect, which strikingly correlates with the phenotypic aggravation of key clinical symptoms after episodes of high fever. We performed induced pluripotent stem (iPS) cell reprogramming of patient fibroblasts followed by in vitro erythroid differentiation to translate the intriguing molecular defect to phenotypic expression in relevant tissue, to disclose the molecular basis for some specific TTD features. We observed a clear hematopoietic defect during late-stage differentiation associated with hemoglobin subunit imbalance. These new findings of a DNA repair-independent transcription defect and tissue-specific malfunctioning provide novel mechanistic insight into the etiology of TTD.
Gesehen am 09.04.2018